Characterisation of novel influenza‐derived HLA‐B*18:01‐restricted epitopes - Samuel Liwei Leong; Lawton Murdolo; Janesha C Maddumage; Marios Koutsakos; Katherine Kedzierska; Anthony W Purcell; Stephanie Gras; Emma J Grant (Clinical & Translational Immunology, 2024)
Abstract Objectives Seasonal influenza viruses cause roughly 650 000 deaths annually despite available vaccines. CD8+ T cells typically recognise influenza‐derived peptides from internal structural and non‐structural influenza proteins and are an attractive avenue for future vaccine design as they could reduce the severity of disease following infection with diverse influenza strains. CD8+ T cells recognise peptides presented by the highly polymorphic Human Leukocyte Antigens class I molecules (HLA‐I). Each HLA‐I variant has distinct peptide binding preferences, representing a significant obstacle for designing vaccines that elicit CD8+ T cell responses across broad populations. Consequently, the rational design of a CD8+ T cell‐mediated vaccine would require the identification of highly immunogenic peptides restricted to a range of different HLA molecules. Methods Here, we assessed the immunogenicity of six recently published novel influenza‐derived peptides identified by mass‐spectrometry and predicted to bind to the prevalent HLA‐B*18:01 molecule. Results Using CD8+ T cell activation assays and protein biochemistry, we showed that 3/6 of the novel peptides were immunogenic in several HLA‐B*18:01+ individuals and confirmed their HLA‐B*18:01 restriction. We subsequently compared CD8+ T cell responses towards the previously identified highly immunogenic HLA‐B*18:01‐restricted NP219 peptide. Using X‐ray crystallography, we solved the first crystal structures of HLA‐B*18:01 presenting immunogenic influenza‐derived peptides. Finally, we dissected the first TCR repertoires specific for HLA‐B*18:01 restricted pathogen‐derived peptides, identifying private and restricted repertoires against each of the four peptides. Conclusion Overall the characterisation of these novel immunogenic peptides provides additional HLA‐B*18:01‐restricted vaccine targets derived from the Matrix protein 1 and potentially the non‐structural protein and the RNA polymerase catalytic subunit of influenza viruses.